Remote work arrangement: a blessing in disguise for socially anxious individuals - Khan, Khalid; e-Habiba, Umm; Aziz, Shahab; Sabeen, Zara; Zeeshan, Asma; Naz, Zareen; Waseem, Muhammad (Frontiers in Psychology, 2024)
This research examines the link between social anxiety disorder (SAD), psychological distance (PD), and burnout using survey data from 463 software development workers who are currently working remotely. According to the results of the study, SAD was associated with higher PD, but, in contrast to what had been shown in earlier studies, this higher PD had no effect on the participants' reported levels of burnout. Both psychological safety and workplace attachment orientation (WAO) were tested for their moderating effects in this study. According to the study's findings, the link between SAD and PD was moderated by WAO but not by psychological safety. The findings of this study underscore the importance of conducting additional research on the challenges faced by people with social anxiety in the workplace and the steps that can be taken by employers to better accommodate them.